Physical Layer-Aware Circuit Reallocation to Prevent Request Blocking in Elastic Optical Networks - Araújo, Selles; Lacerda, Jurandir; Fontinele, Alexandre; Leão, Érico; Reis Júnior, José V. dos; Soares, André (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2023)
This paper proposes a new circuit reallocation algorithm that considers the effects of physical layer in transparent elastic optical networks, called Just One Circuit Reallocation (JOC).The JOC algorithm reallocates just one already established circuit to avoid the blocking of new circuit request due to impairments in the physical layer. The results of the JOC algorithm were compared to three other algorithms: Circuit Reallocation Strategy Physical Layer (CRS-PL), Circuit Reallocation for Block Reduction related to the QoT of the circuits (R-RQoT) and Make-Before-Break (MBBr). The reallocation algorithms are evaluated under the bandwidth blocking probability (BBP), circuit blocking probability (CBP) and the number of reallocated circuits (NRC) for USA and EON topologies. Besides, we also evaluated the performance of reallocation algorithms using Complete Sharing, K-Shortest Path Computation, Modified Dijkstra Paths Computation and K-Shortest Path with Reduction of QoTO to routing and spectrum assignment. Simulation results show that the proposed algorithm exhibits better performance than the CRS-PL, R-RQoT and MBBr algorithms with regard to BBP, PBC and NRC. In terms of BBP, our algorithm presented minimum reductions of approximately 65.36% e 55.6% for the USA and EON topology, respectively.